Gene delivery to Her-2+ breast cancer cells using a two-component delivery system to achieve specificity - Kullberg, Max (2014)
Current liposomal gene delivery systems predominately utilize cationic lipids, which efficiently bind and deliver DNA plasmid, but also result in nonspecific gene expression in lung and liver tissue. To improve specificity, a two-component delivery strategy employing neutral liposomes was used to target breast cancers positive for the human epidermal growth factor receptor 2 (Her-2). The first component consisted of plasmid DNA condensed with cationic polyethylene glycol (PEG) modified polylysine (PL/DNA). The second component was a neutral Her-2 targeting liposome conjugated to the pore-forming protein, Listeriolysin O (LLO). Independently, PL/DNA delivery resulted in low expression of plasmid DNA. However, when PL/DNA and LLO/liposomes co-localized within an endosome, LLO disrupted endosome integrity, leading to cytoplasmic delivery and expression of the plasmid. When used to deliver a plasmid encoding the luciferase gene, this two-component system resulted in gene expression that was 268-fold greater in Her-2 positive cells than in Her-2 negative cells.